2012
DOI: 10.1007/s12020-012-9659-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of angiotensin peptides and angiotensin receptor antagonists on the cell growth and angiogenic activity of GH3 lactosomatotroph cells in vitro

Abstract: The local renin-angiotensin system (RAS) is present in the pituitary gland, and inhibitory effects of angiotensins on the lactosomatotroph (GH3) cell growth have been revealed. The aim of this study was to examine the influence of various angiotensin peptides and angiotensin AT1, AT2, and AT4 receptors antagonists on the cell proliferation, viability, and VEGF secretion in pituitary lactosomatotroph GH3 cell culture in order to identify receptors involved in antiproliferative effects of angiotensins on GH3 tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…All tested antagonists of ATRs (losartan-AT1R antagonist; PD123319-AT2R antagonist; divalinal-AT4R antagonist) were unable to prevent the decrease of total number of the GH3 cells and their proliferation induced by angiotensins. This outcome suggests that growth inhibition induced by angiotensins is not correlated with tested ATRs [56].…”
Section: Pituitary Glandmentioning
confidence: 89%
See 2 more Smart Citations
“…All tested antagonists of ATRs (losartan-AT1R antagonist; PD123319-AT2R antagonist; divalinal-AT4R antagonist) were unable to prevent the decrease of total number of the GH3 cells and their proliferation induced by angiotensins. This outcome suggests that growth inhibition induced by angiotensins is not correlated with tested ATRs [56].…”
Section: Pituitary Glandmentioning
confidence: 89%
“…Addition of AT1R and AT2R antagonists and ACE inhibitor caused diminished the number of VEGF-positive blood vessels [54]. Those outcomes suggested that RAS takes part in stimulation of angiogenesis by induction of VEGF secretion acting by AT1R and AT2R in estrogen-induced adenoma [56]. In another study, the influence of Ang IV on VEGF secretion in GH3 cells was additionally tested.…”
Section: Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Ang-(4-8) is found in the circulation but there are a few reports about the biological function of Ang-(4-8) [ 10 29 ]. Different behavioral effects of Ang II and Ang-(4-8) have been reported in rats [ 29 ] and Ang-(5-8) has been reported to inhibit GH3 rat pituitary tumor cell proliferation independent of both MAPK p44/42 and MAPK p38 [ 30 ]. In the present study, therefore, we investigated the effects of Ang (4-8) on ANP secretion using isolated perfused rat atria.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Ang (5-8) elicits small or no changes of cardiovascular parameters compared to Ang II [8]. However, a recent report showed that Ang (5)(6)(7)(8) is effective in the regulation of cellular proliferation [50]. Importantly, we have previously demonstrated that Ang (5)(6)(7)(8) contains the smallest amino acid sequence that is necessary and sufficient to elicit a strong, dose-dependent and region-specific modulation of antinociceptive effect upon injection into the vlPAG [8].…”
Section: Introductionmentioning
confidence: 93%